An occurrence of villiaumite in the Ilímaussaq Intrusion, South Greenland - Bondam, Jan; Ferguson, J. (Meddelelser om Grønland, 1962)
Villiaumite was found in drill cores from the Ilímaussaq Intrusion, South Greenland. The villiaumite is found in parageneses which have undergone alteration and in late stage, analcime-rich veins occurring in the per-alkaline rocks, lujavrite and naujaite. Villiaumite is the last formed mineral, crystallizing in a comparatively water-rich environment. Chemical analysis: F = 44.81, Na= 54.23 , insoluble 0.80. Spectrographic data: 100 ppm Al; Jess than 100 ppm Si, Ca and Mg ; 50 ppm Mn. Villiaumite in this occurrence is cubic; a = 4.633 Å. R. I. = 1.325